Knowledge about family planning in higher education students - Paula Nelas; Emilia Coutinho; Cláudia Chaves; Odete Amaral; Carla Cruz (INFAD, 2018)
Background: Family planning promotes activities that ensure sexual and reproductive health, ensuring information that promotes a safe and healthy sexuality experience Objectives: To determine if sociodemographic, affective and sexual variables influence the knowledge about family planning in higher education students Methodology: This is a quantitative, cross-sectional, descriptive and correlational study with a sample of 199 higher education students, with a mean age of 20.89 years (sd = ± 2.01 years), mostly female (76.4%). The data collection instrument was a questionnaire that enabled the construction of the sociodemographic, affective and sexual characterization. The Family Planning Knowledge Scale (Nelas, Silva, Ferreira, Duarte Chaves, 2010) was also included. The ethical procedures were guaranteed. The data was processed with the SPSS program (Statistical Package for the Social Sciences) version 24 for Windows. Results: More than half (86.9%) have initiated their sexual life. The majority of these (78.6%) reported the onset at 16-20 years. Most of them (61.8%) have no dating relationship at present, and 60.3%. have no sex in the current relationship. 90.5% use contraception. The majority (95.0%) would use condoms in occasional relationships. 55.8% of the participants do not monitor sexual and reproductive health and the nurse clarifies doubts about sexual and reproductive health with 75.4% of the sample. 63.1% of the participants never did a cervical cytology. 56.8% are not aware of family planning. Girls report more knowledge about family planning (p = 0.034). The monthly income of the household is statistically significant, with the highest income students showing more knowledge (p = 0.047). Health students have more knowledge (p = 0.001). Of the affective and sexual variables, only the sexual life had statistical significance, with those that had not initiated it, having more knowledge (p = 0.014). Conclusion: There is a need for interventions to promote sexual and reproductive health, aiming at a healthy sexuality experience.